Nutritional requirements and feed management of meat type ducks. Issue 1 (March 2016) - BAÉZA, E.
Abstract : This review discusses the different duck species and their feeding management used in meat production in various countries. The initial review describes the requirements of meat type ducks for energy, proteins and amino acids and minerals, vitamins and trace-elements. Other areas discussed include recommendations regarding feed management (feed presentation, feed restriction, use of enzymes and feedstuffs, fatty acid composition of diets). The main breeds used for meat production in the world are Pekin, Muscovy and mule ducks. As growth rate, efficiency and body composition of these three genotypes are different, the specific features of each type of duck are examined when reared under intensive production systems.